Strategic Information Systems Planning for RFID Implementation in Hajj Management Systems - Al-Hashedi, Abdullah Hussein; Arshad, Muhammad Rafie Hj Mohd; Baharudin, Ahmad Suhaimi; Mohamed, Hasimah Hj; Osman, Omar (IEEE, 2014)
The growing number of radio frequency identification (RFID) applications in various industrial fields makes the development of strategic information systems planning (SISP) for the implementation process is essential. Hajj (pilgrimage) sector is one of sectors that would benefit from RFID system implementation through several applications. Without a good plan for the implementation process, it would be difficult to reap a lot of benefits expected from the use of this technology. For this reason, this study proposed a model of SISP for RFID implementation in Hajj management systems. This model assists Hajj management authorities and any related Hajj organization wishing to implement RFID system to better understand and prepare for RFID implementation. It provides guidelines for RFID implementation in Hajj management systems with an emphasis on implementation issues that are needed to be considered such as RFID implementation scenario and RFID data sharing. We hope that the proposed model will provide Hajj organizers with knowledge needed for the implementation of RFID technology in Hajj management.